Catalytic Synthesis of 2-(1-Cyclohexenyl)cyclohexanone by Mixed Heteropoly Acids Catalyst (PW12 + PMo12/SBA-15) - Wang, Ying-Ying; Wu, Bo; Liu, Chun-Li; Li, Fu-Xiang; Lv, Zhi-Ping; Xue, Jian-Wei (Asian Journal of Chemistry, 2014)
Mixed heteropoly acids (phosphotungstic acid and phosphomolybdic acid) supported on SBA-15 (PW12 + PMo12/SBA-15) by impregnation method was used as catalysts of self-condensation reaction of cyclohexanone to synthesize the 2-(1-cyclohexenyl)cyclohexanone. The experimental results indicated that the mixed heteropoly acids supported on SBA-15 had effective catalytic performance, which catalytic synthesis of 2-(1-cyclohexenyl)cyclohexanone. The effects of various parameters on the conversion ratio such as the amount of catalyst, loading amount, reaction time and reaction temperature were investigated. The optimum reaction conditions were as follows: The loading of the PW12 + PMo12/SBA-15 was 29 %, the percentage of catalyst in reactants was 3 %, the reaction time was 2.5 h and the reaction temperature was 150 °C. The conversion rate could reach 86.5 %.